2013
DOI: 10.1002/adfm.201300918
|View full text |Cite
|
Sign up to set email alerts
|

Materials‐Scale Implications of Solvent and Temperature on [6,6]‐Phenyl‐C61‐butyric Acid Methyl Ester (PCBM): A Theoretical Perspective

Abstract: The ability to detail how molecules pack in the bulk and at the various materials interfaces in the active layer of an organic solar cell is important to further understanding overall device performance. Here, [6,6]‐phenyl‐C61‐butyric acid methyl ester (PCBM), a preferred electron‐acceptor material in organic solar cells, is studied through molecular dynamics (MD) simulations; the goal is to examine the effects of temperature and trace solvents on the packing and morphological features of bulk PCBM. Solubility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 91 publications
4
50
0
Order By: Relevance
“…24 For simulations of the pure fullerene derivatives, 400 molecules were randomly placed in the box and simulated at 1000 K for at least 2 ns. The resulting amorphous structures were then equilibrated at 300 K for at least 10 ns.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…24 For simulations of the pure fullerene derivatives, 400 molecules were randomly placed in the box and simulated at 1000 K for at least 2 ns. The resulting amorphous structures were then equilibrated at 300 K for at least 10 ns.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%
“…Miscibility parameters (i.e., Hildebrand parameters) and surface energies for the fullerenes were computed as previously described. 24 P3HT was modeled using modified OPLS-AA parameters. [44][45] Simulations of P3HT:fullerene mixtures were carried out with 50-monomer P3HT chain lengths (8.32 kDa) at weight-percent's of P3HT of 25% (11 P3HT oligomers and either 328 ICMA or 302 PCBM), 50% (23 P3HT oligomers and either 229 ICMA or 210 PCBM molecules), and 75% (34 P3HT oligomers and either 117 ICMA or 104 PCBM molecules).…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigated systems are pristine C 60 , phenyl-C 61 -butyric acid methyl ester (PCBM; properties of an isolated molecule, 46,47 solid state organization as pure crystals and co-crystals, [48][49][50][51][52][53][54][55] and in liquid media 56,57 ) and a homologues series of N-substituted fulleropyrrolidines (FPs), which differ in a number of straight methylene groups-CH 2 -in a side chain. These molecules vary from each other in shape and polarity; therefore, they appear to be good candidates for the study of effects of functionalization on the hydration of fullerenes.…”
Section: Introductionmentioning
confidence: 99%
“…The OPLS-AA 24 (Optimized Potentials for Liquid Simulations-All Atom) force-field parameters were used to simulate the fullerenes, as we and others have shown that this force field 5 accurately predicts many of the bulk properties of C 60 , PCBM, and indene-C 60 11, 18, 20, 21, 25-27 Simulations of amorphous PCBM and mono-indene-C 60 have been described in our previous publications. [26][27][28] The phenyl-butyric acid methyl ester adduct (C 12 H 14 O 2 ) induces a dipole moment in PCBM, whose magnitude (between 1.5 and 5 D) varies with the orientation of the ester group with respect to the phenyl group; the indene adduct (C 9 H 8 ) brings a dipole moment of ca. 3 D. We have recently shown that these variations in adduct polarity affect the cohesive characteristics of pure fullerene and P3HT:fullerene blend thin films.…”
Section: Computational Detailsmentioning
confidence: 99%